0.003(9-k)+0.05(k-6)=1

Simple and best practice solution for 0.003(9-k)+0.05(k-6)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.003(9-k)+0.05(k-6)=1 equation:



0.003(9-k)+0.05(k-6)=1
We move all terms to the left:
0.003(9-k)+0.05(k-6)-(1)=0
We add all the numbers together, and all the variables
0.003(-1k+9)+0.05(k-6)-1=0
We multiply parentheses
-0.003k+0.05k+0.027-0.3-1=0
We add all the numbers together, and all the variables
0.047k-1.273=0
We move all terms containing k to the left, all other terms to the right
0.047k=1.273
k=1.273/0.047
k=27+0.004/0.047

See similar equations:

| -2(x+5)+6x=3(x+1)+x+7 | | 15-8a=8a | | 2w+24=54 | | Y=x+0.2x | | 6y-39=-9 | | 6=7-m+7m-9 | | 5x-3-4x+2=9x+3 | | 0.003(3-k)+0.04(k-4)=1 | | 12x^2+3x-15=0 | | W-(3x-4)=2x-9 | | 2x+7=1x+8 | | -243=-90+3x | | 12-4e=4 | | 4x+3=- | | 54=x/4+47 | | 2x+7=2x+0 | | 7(x-5)=16 | | x/2+2/3=1/4 | | 1/2(21-13k)=15 | | 2x=5x+8x | | -10+12x=6x+10 | | -17=-9+4yy= | | x+(x-2)-30=2630 | | (7x-9)=(2x+36) | | 38(p+25)=4218 | | 6x+22x-7=7(4x+8) | | 6(x+17)=1074 | | 3t2+6t=183t2+6t=18 | | 4(x+19)=760 | | r+4=16 | | 7+5/9x=2/3 | | 2x+9+3x-1=-2 |

Equations solver categories